2012
DOI: 10.4103/0970-9290.100414
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of def index with Nyvad′s new caries diagnostic criteria among three to six years old children in a school at Bangalore city

Abstract: The result obtained by Nyvad's new caries diagnostic criteria produces values much higher than those with def caries index system. Hence, Nyvad's new caries diagnostic criteria can be used to diagnose dental caries at the initial stages, which in turn will reflect exact prevalence of caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Inspite of this, we observed that the severity of dental caries in the deciduous teeth increased markedly along with the age of the children. Similar data were reported using the pufa index in 5- to 7-year-olds in the Bialystok district in Poland [ 21 ] and in a study by Shankar et al [ 22 ] using the def index in a group of Indian children. The results clearly show that the neglect of caries treatment at an early stage increases the risk and severity of its clinical consequences over time.…”
Section: Discussionsupporting
confidence: 86%
“…Inspite of this, we observed that the severity of dental caries in the deciduous teeth increased markedly along with the age of the children. Similar data were reported using the pufa index in 5- to 7-year-olds in the Bialystok district in Poland [ 21 ] and in a study by Shankar et al [ 22 ] using the def index in a group of Indian children. The results clearly show that the neglect of caries treatment at an early stage increases the risk and severity of its clinical consequences over time.…”
Section: Discussionsupporting
confidence: 86%
“…Several standardized dental assessment criteria are available and widely used to evaluate dental caries through visual-tactile examination, e.g., decayed/missing/filled teeth/surfaces (DMFT/S) [57][58][59][60]; the International Caries Detection and Assessment System (ICDAS) core criteria I and II [61][62][63]; and Nyvad Caries Diagnostic Criteria [64][65][66]. Imaging modalities include radiographs and digital photography.…”
Section: Impact Of Socioeconomic Status (Ses) On Dental Outcomes In Hmentioning
confidence: 99%
“…Only a few epidemiological studies have been conducted and reported in such centers. The existing studies in India conducted among preschool children have used WHO criteria and Nyvad's new diagnostic criteria in detecting caries. ICDAS is currently a recommended method for detecting caries and has been found to be feasible in epidemiological surveys conducted in preschool children.…”
Section: Discussionmentioning
confidence: 99%